2015
DOI: 10.1371/journal.pone.0121547
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of NF-κB/miR-21/PTEN Pathway Sensitizes Non-Small Cell Lung Cancer to Cisplatin

Abstract: BackgroundPlatinum-based chemotherapy is a standard strategy for non-small cell lung cancer (NSCLC), while chemoresistance remains a major therapeutic challenge in current clinical practice. Our present study was aimed to determine whether inhibition of the NF-κB/miR-21/PTEN pathway could increase the sensitivity of NSCLC to cisplatin.MethodsThe expression of miR-21 in NSCLC tissues was determined using in situ hybridization. Next, the effect of miR-21 on the sensitivity of A549 cells to cisplatin was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 30 publications
7
56
0
Order By: Relevance
“…Yang et al demonstrate that NF‐κB up‐regulates the expression of miR‐21, by binding to its gene promoter 49. Other studies also document NF‐κB binding sites on the promoter of miR‐21 34, 50.…”
Section: Discussionmentioning
confidence: 98%
“…Yang et al demonstrate that NF‐κB up‐regulates the expression of miR‐21, by binding to its gene promoter 49. Other studies also document NF‐κB binding sites on the promoter of miR‐21 34, 50.…”
Section: Discussionmentioning
confidence: 98%
“…They have identified an inverse correlation between miR-21 and PTEN protein in tumor tissue and further showed that miR-21 post-transcriptionally down-regulates the expression of tumor suppressor PTEN and stimulates growth in NSCLC cells [40]. Later on, the regulatory axis of miR-21 and PTEN in NSCLC has been confirmed by follow-up studies [38,39,48,49,50]. Nevertheless, the regulation of SMAD7, and subsequently TGFβ receptor signaling, has not been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, miR-21 targets multiple genes in mTOR pathway, including PTEN, p85α and PDCD4. Besides promoting malignant growth, the miR-21/PTEN/PI3K/AKT/mTOR axis has been shown to influence anti-cancer effects of zoledronic acid [80] , triptolide [81] , Metformin [82] , Matrine [83] and curcumin [84] , and modulate radiosensitivity [85, 86] and chemosensitivity to tamoxifen, fulvestrant [87] , sorafenib [88] , cisplatin [89, 90] , imatinib [91] , gefitinib [92] , doxorubicin [93] , daunorubicin [94] , anti-EGFR tyrosine kinase inhibitors (TKI) [95] and the CHOP chemotherapy regimen [96] . miR-21 also influences PI3K/AKT/mTOR signaling via PIK3R1 that negatively regulates p110 subunit under certain circumstances.…”
Section: Mirnas That Activate Mtor Pathwaymentioning
confidence: 99%